Problems of the Mutual Interaction Between National Cultures in “Christianity Age” (1549-1614) in Japan - Račelis, Svajūnas (Acta Orientalia Vilnensia, 2002)
This article is intended to be a study of some problems of mutual interaction between national cultures in the period known usually as “Christianity age”. Contacts with Western culture had a tremendous importance in the Japanese history having laid some foundations of Meiji age Japan and its culture.During this period the Japanese won a free access to cultural achievements of the West. The author traces the trends of social changes in the society of Japan, cultural developments and the spread of Christianity at that time. Accordingly, much attention is given to the evaluation of the impact of new concepts to mental world of Japanese people.A considerable part of the article is dedicated to the problem of mutual interaction between Buddhism and newly introduced Christianity.The author underlines a remarkable characteristic of Japanese culture - its adaptivity to foreign influences and at the same time a striking continuity of national cultural tradition.The article reveals the unique process of amalgamation of ancient national culture and the newly introduced Western achievements and ideas resulting in moulding the basis of the latest crucial changes in the society of Japan in Meiji period (1868-1912).